A satisfação dos clientes internos e o comprometimento organizacional: um estudo à luz do modelo ASH nas indústrias alimentícias do RN - Bertoldo, Marisa Rios (2006)
Currently the organizations are passing for continuous cycles of changes due to necessity of survival in the work market. The administration of the future points a way to the organizations of today and tomorrow, the search of the competitiveness from loyalty and motivation of its staff. Of this form, the model of the Auditoria do Sistema Humano (ASH), developed for Spanish researchers and that now it is being applied in Brazil, contemplates a series of dimensions about Human Resources management quality in the companies and the organizational effectiveness, such as the environment where the company is inserted, the strategies, the organizational drawing, the psychological and psychosocial processes, e the reached results. In this direction, the present research analyzed the factors of job satisfaction and organizational commitment, making, also, a relation of causality between the same ones. The quantitative-descriptive research had as population the employees of twenty three nourishing industries of the State of Rio Grande do Norte (Brazil), registered in the Federacy of the Industries of the state. The collection of the data occurred for the months of October of 2005 and March of 2006, by means of the application of questionnaire of model ASH. The sample was composed for 197 employees, however it was observed presence of five outliers, that they had been excluded from the analysis of the data. To extract the dimensions of the satisfaction and the commitment and identification the factorial analysis was used, with extraction method of principal components, rotation Varimax and normalization Kaiser. The gotten dimensions had been evaluated with the calculation of the coefficient Alpha of Cronbach. The factorial analysis of the pointers of the organizational commitment and identification had extracted ten factors. Of these, four had gotten significance of the analyses inside: affective commitment, values commitment, continuance commitment and necessity commitment. The result of the analysis of the pointers of job satisfaction indicated four factors: extrinsic, motivations, relation with the friends and auto-accomplishment. To deal with the data the relation between job satisfaction and organizational commitment it was used technique of multiple regression. The correlation between commitment and satisfaction was satisfactory, detaching the affective commitment with bigger index of correlation, followed of the affective one